Dentofacial characteristics of children and adolescents with foetal alcohol spectrum disorders: a comparison with matched controls - Katarzyna Ludwików; Anna Westerlund; Nameer Al-Taai; Małgorzata Zadurska; Ewa Monika Czochrowska (SpringerOpen, 2023)
Abstract Background Foetal alcohol spectrum disorders (FASD) include somatic and neurological developmental disturbances after prenatal alcohol exposure, including facial anomalies. However, the knowledge of the orthodontic skeletal and dental cephalometric relations in this group is limited. The aim of the study was to assess the dentofacial characteristics of children and adolescents with FASD and to compare them with a matched control group. Methods The study group comprised all available children and adolescents diagnosed with FASD (> 7 years of age) in whom good quality cephalograms were available. The control group comprised non-syndromic, orthodontically untreated children with normal occlusion and skeletal relations matched with age and gender. Cephalometric analysis included eighteen linear and angular measurements. The general linear model for repeated measures regarding age, gender and the type of FASD was applied. Results The group with FASD included 35 individuals (21 girls and 14 boys) aged 7-18 years including 21 with foetal alcohol syndrome. The mean age in the study and the control group was 12.8 years (SD, range 3.2, 7.1-18.1) and 13.0 (SD, range 2.9, 9.1-18.1), respectively. Statistically significant differences between the groups were found in 15 out of 18 of the cephalometric measurements (83%). In children with FASD the mandible was more retrusive, the incisors were more proclined and the mandibular incisors and the lips were more protruded when compared with controls. There was no significant evidence of an influence of age, gender or FASD type. Conclusions Dentofacial characteristics of children and adolescents with FASD significantly differ from controls. Early orthodontic diagnosis and prophylaxis should play a part of the interdisciplinary care of patients in this group.